2009
DOI: 10.1002/cncr.24088
|View full text |Cite
|
Sign up to set email alerts
|

Association of progression‐free survival, overall survival, and patient‐reported outcomes by skin toxicity and KRAS status in patients receiving panitumumab monotherapy

Abstract: More severe ST, by both clinical grading and PRO, is associated with better CRC symptoms and HRQOL and with longer OS and PFS among panitumumab-treated patients. The associations for PFS were more pronounced in patients with WT KRAS tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 28 publications
(55 reference statements)
4
79
0
3
Order By: Relevance
“…For both cetuximab (2) and panitumumab (35), a correlation between skin toxicity and survival was reported. In the present study, such a relationship was observed but it did not reach statistical significance (P ¼ 0.077).…”
Section: Discussionmentioning
confidence: 99%
“…For both cetuximab (2) and panitumumab (35), a correlation between skin toxicity and survival was reported. In the present study, such a relationship was observed but it did not reach statistical significance (P ¼ 0.077).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were excluded from the analysis: one study used an egfri in both arms 13 , one did not present rash rates according to either grades 3 and 4 criteria or allgrades criteria 14 , and one study was a duplicate of another study 15 . Thus thirteen studies were eligible for inclusion in the meta-analysis ( Table ii).…”
Section: Resultsmentioning
confidence: 99%
“…In 2010, the FOLFIRI/panitumumab combination was compared to FOLFIRI alone in second-line treatment. In the KRAS-wt patients, when panitumumab was added to FOLFIRI median PFS was 5.9 months versus 3.9 months for FOLFIRI alone (p=0.004) (Peeters et al 2009). Panitumumab, in conjunction with chemotherapy regimen, has also been evaluated in firstline therapy for mCRC.…”
Section: Panitumumab (Table 3)mentioning
confidence: 98%